Clinical features, etiology and outcomes of community-acquired pneumonia in patients with chronic obstructive pulmonary disease. - Joan Gómez-Junyent (Public Library of Science (PLoS), 2014)
Background Community-acquired pneumonia (CAP) is a frequent complication of chronic obstructive pulmonary disease (COPD), but previous studies are often contradictory. Objectives We aimed to ascertain the characteristics and outcomes of CAP in patients with COPD as well as to determine the risk factors for mortality and Pseudomonas aeruginosa pneumonia in COPD patients with CAP. We also describe the etiology and outcomes of CAP in COPD patients receiving chronic oxygen therapy at home and those receiving inhaled steroids. Methods An observational analysis of a prospective cohort of hospitalized adults with CAP (1995-2011) was performed. Results We documented 4121 CAP episodes, of which 983 (23.9%) occurred in patients with COPD; the median FEV1 value was 50%, and 57.8% were classified as stage III or IV in the GOLD classification. Fifty-eight per cent of patients were receiving inhaled steroids, and 14.6% chronic oxygen therapy at home. Patients with COPD presented specific clinical features. S. pneumoniae was the leading causative organism overall, but P. aeruginosa was more frequent in COPD (3.4 vs. 0.5%; p<0.001). Independent risk factors for case-fatality rate in patients with COPD were multilobar pneumonia, P. aeruginosa pneumonia, and high-risk PSI classes. Prior pneumococcal vaccination was found to be protective. FEV1 was an independent risk factor for P. aeruginosa pneumonia. Conclusions CAP in patients with COPD presents specific characteristics and risk factors for mortality. Prior pneumococcal vaccine has a beneficial effect on outcomes. P. aeruginosa pneumonia is associated with low FEV1 values and poor prognosis.